Internalization of Character Values of CÃ‘ÂpÃ‘Âtan Dance Performance at Manunggal Putra Budaya Group in Karanggayam District Kebumen Regency - Hapsari, Wahyu Ratri; Lestari, Wahyu; Sunarto, Sunarto (Catharsis, 2019)
Cèpètan dance as one of arts of Karanggayam society is full of values in its performance. The values here means part of character values. Character values are indirectly able to internalize the actors that learn the Cèpètan dance. There is something interesting in this group, i.e. the dancers are children. It is hoped that the values behind this dance can build the children’s character. The research aimed at knowing the form of performance and internalization character values that reflect in Cèpètan dance. To analyze the internalization, the writer uses Koentjaraningrat’s theory (1990) about inheriting. The approach used in this research is qualitative with phenomenology design. The data collecting techniques are observation, interview, and literature observation. The data validity used triangulation technique, they are source triangulation, and method triangulation. The data was analyzed through reduction, presentation, and verification. From the results show that the character values of Cèpètan dance performance reflects the values of creativity, discipline, and responsibility.